Analysis of the relationship between job satisfaction and organizational trust of physical education and sports teachers - Murat Aygün (Journal of Pedagogical Research, 2021)
Job satisfaction and organizational trust emerge as just two of the important factors that can lead all institutions to success today. The objective of this research is to analyse, the relationship between job satisfaction and organizational trust of physical education and sports teachers pursuant to some demographic variables. The research group consists of 146 physical education and sports teachers working in schools. Personal information forms, "Minnesota Satisfaction Questionnaire" and "Organizational Trust of School Scale" have been used as data collection tools. Pearson moments correlation coefficients have been tackled for the relationship between organizational trust and job satisfaction. It has been observed that there was a positive, significant relationship between job satisfaction and organizational trust in the research findings (p<.05 ). As a result of the research, it has been predicted that factors such as the individual's location, psychological and environmental factors, working conditions, and communication have an active role in determining the relationship between job satisfaction and organizational trust.